Создание кафедры археологии и музееведения в Киевском университете - Самойленко, Л.Г. (Археологія і давня історія України, 2012)
В статье изложены некоторые аспекты создания и первых лет работы кафедры археологии и музееведения Киевского национального университета имени Тараса Шевченко. У статті викладені деякі аспекти створення (1944)
кафедри археології та музеєзнавства Київського національного університету імені Тараса Шевченка.
Висвітлюються проблеми організації роботи кафедри в перші роки діяльності, формування викладацького складу, навчальних курсів, програм і методичних посібників. Крім загальних тенденцій розвитку
історичної науки в Радянському Союзі на формування кафедри вплинули особистості як її засновника
Л.М. Славіна, так і його колег. Першими викладачами кафедри були В.А. Богусевич і А.В. Добровольський. У 1950 р. аспірантуру при кафедрі закінчили
учні Л.М. Славіна молоді фахівці М.М. Бондар і
Г.Г. Мезенцева. Вони стають асистентами кафедри, а згодом — доцентами та професорами, продовжуючи справу свого вчителя. This article is devoted to some aspects of the foundation
(1944) and first years of work of the Department of
Archaeology and Museum Studies at Taras Shevchenko
National University of Kiev. The author shows problems
in the process of forming the magisterial staff, the
curricula, handbooks and the development of learning
materials.
In addition to the general tendency of the development
of historical science in the USSR, the personal
quality of the founder of the department, L.M. Slavin
and his associates affected the formation process of this
department. The first teachers in this department were
V.A. Bogusevich and A.V. Dobrovolsky. The young students
of professor Slavin - young specialists N.N. Bondar
and G.G. Mezanceva finished their postgraduate studies
in the beginning of 1950. They became the assistants of
the department of archaeology and then lecturers and
professors, continuing the work of their teacher.